Collective irrigation network analysis considering plots irrigation scheduling - Francisco Aldiel Lima; Juan Ignacio Córcoles; Jose Maria Tarjuelo; Angel Martinez Romero (Ingeniería del Agua)
The aim of this work is to implement a simulation tool for management of collective irrigation network, than minimizes the energy cost in pumping station. The proposed methodology has been applied in 2015 to an irrigation network of 550 ha in Castilla-La Mancha, for two pressure head managements (fixed or variable), taking into account the open hydrants and their location in the network. The tool simulates the network behavior using EPANET®, and it is based on the crops irrigation scheduling of the plots calculated with MOPECO model. The results indicate that the use of fixed pressure head management might be more interesting than the variable pressure head, due to its simplicity, despite its slight increase in energy consumption, lower than 2% in the analysed cases.